Հայրենիք—սփիւռք առաջին համաժողովը - Խաչատրեան, Անի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
24-27 ноября 1980 года в Ереване, столице Армении, проводился первый всеармянский конгресс. Этот беспрецедентный съезд объединил более 100 представителей армянской диаспоры из более 30 стран мира. В конгрессе также участвовали Католикос Всех Армян Вазген I и другие представители духовенства. Участие Армянской Апостольской Церкви в конференции было важным, так как на протяжении веков Церковь играла важную роль в сохранении армянской идентичности. После формирования армянской диаспоры, Армянская Апостольская Церковь успешно продолжала носить свою важнейшую функцию в армянских общинах в различных странах. The first Pan-Armenian congress began its work in Yerevan on 24—27 November, 1980. This unprecedented event brought together more than 100 representatives of the Armenian Diaspora from more than 30 countries of the world. The Catholicos of All Armenians Vasken I and other Brotherhood members also participated in the congress. The participation of the Armenian Apostolic Church in the congress was important: for centuries, the Church had played an important role in preserving the Armenian identity. After the formation of the Armenian Diaspora, the Armenian Apostolic Church successfully continued her most important function in contributing to the Armenian communities in various countries.
Keywords: Armenian Diaspora